1997
DOI: 10.1172/jci119280
|View full text |Cite
|
Sign up to set email alerts
|

Superinduction of cyclooxygenase-2 activity in human osteoarthritis-affected cartilage. Influence of nitric oxide.

Abstract: Cartilage specimens from osteoarthritis (OA)-affected patients spontaneously released PGE 2 at 48 h in ex vivo culture at levels at least 50-fold higher than in normal cartilage and 18-fold higher than in normal cartilage ϩ cytokines ϩ endotoxin. The superinduction of PGE 2 production coincides with the upregulation of cyclooxygenase-2 (COX-2) in OA-affected cartilage. Production of both nitric oxide (NO) and PGE 2 by OA cartilage explants is regulated at the level of transcription and translation. Dexamethaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
285
0
8

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(308 citation statements)
references
References 34 publications
13
285
0
8
Order By: Relevance
“…One of the genes that is upregulated in the inflammation process and has been implicated in osteoarthritis and colon cancer is the COX-2 enzyme. [36][37][38] Studies from our laboratory and others have shown that COX-2 activity increases dramatically in colon cancer tissues. 39 Since COX-2 is upregulated both in osteoarthritis and colon cancer, SAM seems to have a positive beneficial effect on both of these chronic diseases.…”
Section: Discussionmentioning
confidence: 98%
“…One of the genes that is upregulated in the inflammation process and has been implicated in osteoarthritis and colon cancer is the COX-2 enzyme. [36][37][38] Studies from our laboratory and others have shown that COX-2 activity increases dramatically in colon cancer tissues. 39 Since COX-2 is upregulated both in osteoarthritis and colon cancer, SAM seems to have a positive beneficial effect on both of these chronic diseases.…”
Section: Discussionmentioning
confidence: 98%
“…Isolation of Bovine and Human Chondrocytes-Bovine cartilage was obtained from young calves, and chondrocytes were isolated from hooves by standard methods with minor modifications (11,12). The released cells were suspended in RPMI 1640 ϩ 10% FBS ϩ antibiotics and plated in a 24-well plate (Becton Dickinson, Lincoln Park, NJ) at a density of 5 ϫ 10 5 cells/2.0 cm 2 for 48 h. Human chondrocytes were isolated from OA-affected cartilage.…”
Section: Methodsmentioning
confidence: 99%
“…Organ Culture of OA Cartilage and Analysis of Mediators-Organ culture was carried out as described previously (11,13). Briefly, knee articular cartilage from patients undergoing knee replacement surgery was obtained and cut in 3-mm discs, and four to six discs (ϳ100 mg) were placed in organ culture in 2 ml of Ham's F-12 medium ϩ 0.1% human albumin for 24 -72 h, with or without modulators.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-1b and PGE 2 concentration are markedly elevated in the synovial fluid of patients with rheumatoid arthritis (RA) (3) and osteoarthritis (OA) (4)(5)(6). Chondrocytes from human OA cartilage explants spontaneously produce PGE 2 (7).…”
mentioning
confidence: 99%